Case report: Applicability of breastfeeding the child of a patient with kidney failure with replacement therapy - Kondakova, Elena V.; Filat’eva, Anastasia E.; Lobanova, Nadezhda A.; Nagaev, Egor I.; Sarimov, Ruslan M.; Gudkov, Sergey V.; Vedunova, Maria V. (Frontiers in Medicine, 2023)
This case report highlights the benefit or harm of breastfeeding in a patient with Kidney Failure with Replacement Therapy (KFRT) undergoing program hemodialysis. This is a unique clinical case, as pregnancy and successful delivery are rare in this group of females. With a favorable outcome, the possibility of breastfeeding is especially relevant for doctors and the mother. The patient was a 31-year-old female who was diagnosed in 2017 with end-stage renal disease associated with chronic glomerulonephritis. Against the background of hemodialysis, pregnancy, accompanied by polyhydramnios, anemia, and secondary arterial hypertension, occurred in 2021. At 37 weeks, a healthy, full-term baby girl was born, and breastfeeding was started. In this study, we conducted a detailed analysis of toxic substances and immunologically significant proteins using high-tech analysis methods. In addition, we studied different portions of milk before and after hemodialysis at different time intervals. After a wide range of experiments, our study did not reveal an optimal time interval for breastfeeding a baby. Despite the decrease in the level of the major uremic toxins 4 hours after the hemodialysis procedure, their level remained high. In addition, the content of nutrients did not reach acceptable limits and the immune status was characterized as pro-inflammatory. In our opinion, breastfeeding is not advisable for this group of patients since the concentration of nutrients is low, and the content of toxic substances exceeds the permissible limits. In this clinical case, the patient decided to stop breastfeeding one month after delivery due to insufficient breast milk and the inability to express it in a certain period of time.